Brucelose bovina: anticorpos bloqueadores da aglutinação e resistentes ao 2-Mercaptoetanol em soros sanguíneos de bovinos não vacinados e vacinados com as amostras B-19 e 45/20 - Pedro Paulo Ornellas dos Santos (1975)
The agglutination titers found in vaccinated and non-vaccinated bovines were compared by the standart agglutination test (SAT), 2 Mercaptoethanol test (2-ME) and Coombs test. The non-vaccinated animals were divided into three sub-groups: Sub-Group I 467samples of bovine serum whose agglutination titers reached up to 25 U.I., collected from three farms. Sub-Group II 402 samples of bovine serum with titers of 50 U.I. collected from five farms. Sub-Group III 52 samples of bovine serum whose titers were less than 100 I.U. or 100 I.U. or higher than such figure. The animals vaccinated against bovine brucellosis were also divided in three sub groups: Sub group IV 48 samples of bovine serum from eight female calves vaccinated with strain B-19 at the age of one to 11 months collected at different times. Sub group V 20 samples of serum from five adults cows, vaccinates with strain 45/20. Four samples were collected from each cow. Sub group VI Ten samples of serum from five heifers at the age of two to 11 months; vaccinated with strain B-19 challenged at the final third of the gestation period with strain 544. The following results were obtained: 1. Sub Group I Only 1,92% of the animals had agglutination titers of 25 I.U. to the SAT. 2. Sub Group II Agglutination titers of up to 50 I.U. were observed with the SAT, 2-ME and Coombs test. 10,53% of the animals presented titers of 25 I.U. only to the 2-ME or to Coombs test. 3. Sub Groups III e IV An increse of up to three dilutions to the Coombs test in relation to SAT were observed. The titers in relaction to 2-ME were equal or slightly higher than the SAT.